Analisis Implementasi Kebijakan Pemungutan Pajak Bumi Dan Bangunan Perdesaan Dan Perkotaan (PBB-P2) Dalam Upaya Meningkatan Penerimaan Pajak Daerah Di BPPRD Kota Baru Jambi Tahun 2021-2022 - Fiatri, Lisa Arisa; Darmawan, M. Bobby R. (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
The research aims to analyze the implementation of Land and Building Tax in Rural and Urban Areas (PBB-P2) and to identify the challenges faced and the efforts made to overcome those challenges in the collection of Land and Building Tax in BPPRD New Jambi City in 2021- 2022. The study adopts a qualitative approach, and the data collected consists of interviews with key informants and documentation. The findings of the research indicate that the implementation of PBB-P2 has been optimally carried out in improving the compliance of individual Taxpayers, as evidenced by the significant increase in tax revenue realization in 2021- 2022. However, there are challenges encountered both internally and externally in the implementation process. To address these challenges, preventive measures are taken by providing information and education to taxpayers in every village to ensure compliance with the tax collection regulations. Additionally, the necessary facilities, decision letters, and field teams are prepared to enhance compliance and public awareness in paying taxes.